ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP KINERJA BENDAHARA SERTA DAMPAKNYA TERHADAP PENYERAPAN ANGGARAN ORGANISASI PERANGKAT DAERAH PADA PEMERINTAH KABUPATEN TABANAN - sukerni, ni wayan wayan; Marhaeni, I.A.A.N. (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.07.NO.11.TAHUN 2018DO - 10.24843/EEB.2018.v07.i11.p01, 2018)
With the enactment of regional autonomy, has provided an opportunity for the Regional Government to organize all government affairs in accordance with its potential. One of the goals in governance is the transparency of government officials in the implementation of budget absorption. The result of evaluation of Performance Accountability Report of Tabanan Regency Government Institution Year 2016, got B rating, and opinion obtained is Unqualified. Behind the predicates and opinions obtained are still many recommendations that need to get the attention of the parties related to the management of local finances, especially treasurer. This study aims to: (i) analyze the effect of facility completeness, quality of human resources, working environment conditions, and treasurer's characteristics to the performance of the treasurer; (ii) to analyze the effect of facility completeness, quality of human resources, working environment condition, treasurer's characteristic, and performance of treasurer to the absorption of regional budget of Organization of Region (OPD) at Tabanan Government; (iii) analyze the indirect effect of facility completeness, quality of human resources, working environment condition and characteristics of treasurer towards absorption of OPD budget through treasurer performance at Tabanan regency government. This research uses Structural Equetion Modell (SEM) PLS analysis. The total number of treasurers studied in this study totals 56 respondents. The results of the analysis show; (ii) facility completeness, quality of human resources and working environment condition, and performance of treasurer have positive and significant influence on the performance of the treasurer, the quality of human resources, the condition of the working environment, and the characteristics of the treasurer have a positive and significant influence on the performance of the treasurer. on the absorption of OPD budget in Tabanan regency government but characteristic of treasurer does not significantly influence budget absorption, (iii) completeness of facility, quality of human resources and condition of work environment and treasurer characteristics significantly and positively influence on absorption of OPD budget at Tabanan regency through performance treasurer.